Sebuah Pengantar Studi Tantangan Pemikiran Kontemporer di Sektor Pertanian - Daru Nurdiana (Universitas Darussalam Gontor, 2018)
This article aims to understand the correlation between agriculture sector and contemporary thought challenge through Islamic worldview perspective. As a basis for food security, agriculture is a vital sector to human life and when agriculture as science, it has the dimensions of nature science and social science. As sector that is the place of interaction between humans and nature, Western and Islam have different perspective on human and nature. Therefore, to understand the challenges of contemporary thought in agricultural sector, this article will describe the matter using four points of discussion, they are understanding farmers and agriculture, the problem of knowledge, the problem of secularism, and the problem of capitalism. Also, this study is an initial introduction to conducting another study of agriculture and Islamic civilization toward the possibility of the need of Islamization of knowledge in agriculture sector.